A Concrete Narration of Self in Society: Book Review of Alienation - Reza Nasiri Hamed (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Alienation has been one of the most important philosophical and social concepts since Hegel’s time, which has been somewhat diminished in recent times. Based on a philosophical and social approach, Rahel Jaeggi in her book takes back the history of alienation to Rousseau’s thought and criticizes his and others’ essentialist approach, arguing that alienation should be surveyed in the context of concrete social relations. In this view, alienation appears when the human relationship with others, including the roles who have taken on, are disrupted, or as Jaeggi stated, they are placed in the “Relation of Relationlessness”. It is clear that man does not have a separate and independent nature from society and its relations and roles until that can be used as a criterion for evaluating the situation of human alienation. Therefore, although social roles and collective relations sometimes lead to human alienation, at the same time, social interactions offer capacities and possibilities for human liberation, and therefore escapement from alienation should not be sought outside the society and its relations.